PERFORMANCE DO MODELO SAFER NA ESTIMATIVA DA EVAPOTRANSPIRAÇÃO REAL DE CULTURAS IRRIGADAS DE FEIJÃO E TRIGO NO CERRADO CENTRAL - Lopes, Juliana Dias; Rodrigues, Lineu Neiva; Scherer-Warren, Morris; Paula, Adriano César Pereira de; Ferreira, Thomás Rocha (IRRIGA, 2021)
PERFORMANCE OF THE SAFER MODEL IN ESTIMATING ACTUAL EVAPOTRANSPIRATION OF WHEAT AND BEAN IRRIGATED CROPS IN THE CENTRAL BRAZILIAN SAVANNAH JULIANA DIAS LOPES1; LINEU NEIVA RODRIGUES2; MORRIS SCHERER-WARREN1; ADRIANO CÉSAR PEREIRA DE PAULA3 E THOMÁS ROCHA FERREIRA4 (1) Agência Nacional de Águas – ANA, Setor Policial, Área 5, Quadra 3, Bloco N, CEP: 70610-200, Brasília, Distrito Federal, Brasil. E-mail: juliana.lopes@ana.gov.br, morris@ana.gov.br; (2) EMBRAPA Cerrados, Rodovia BR-020, Km 18, Caixa Postal 08223, CEP: 73310-970, Planaltina, Distrito Federal, Brasil. E-mail: lineu.rodrigues@embrapa.br; (3) Universidade de Brasília, Campus Universitário Darcy Ribeiro, CEP: 70910-900, Brasília, Distrito Federal, Brasil. E-mail: cesar.adriano087@gmail.com (4) Universidade Federal de Campina Grande, Campus Campina Grande, CEP: 58428-830, Campina Grande, Paraíba, Brasil. E-mail: thomas.ferreira@ufcg.edu.br 1 ABSTRACT Meeting the ever-growing demand for food depends tightly on irrigation. In this scenario, it is essential to manage the scarce water resources available and so to understand the spatial and temporal variation of actual evapotranspiration (ETa). In the past decades, models for monitoring and mapping ETa applying remote sensing data were developed and assessed. In this work, the performance of the Simple Algorithm for Evapotranspiration Retrieving (SAFER) for estimating the evapotranspiration of two annual winter irrigated crops in the Cerrado (Brazilians Savannah) was evaluated. Multispectral and thermal images from the sensors ETM+/Landsat 7 and OLI-TIRS/Landsat 8 were used for this purpose. Initially, the model was calibrated for the wheat crop, then this calibration was tested for the bean crop, using Bowen ration ETa data as reference. After calibration, a coefficient of determination (r2) equal to 0.91 and the root mean square error (RMSE) equal to 0.58 mm d-1 were found for the wheat. For the bean, the r2 was equal to 0.65 and RMSE, equal to 0.77 mm d-1. The results are satisfactory, although they suggest that the model may present an improved performance with specific calibration for each crop and/or region, or adopting calibration in two stages, for lower and higher NDVI values. Keywords: remote sensing, water resources, irrigation, Cerrado. LOPES. J. D.; ROGRIGUES, L. N.; SCHERER-WARREN, M.; PAULA, A. C. P. de; FERREIRA, T. R. PERFORMANCE DO MODELO SAFER NA ESTIMATIVA DA EVAPOTRANSPIRAÇÃO REAL DE CULTURAS IRRIGADAS DE FEIJÃO E TRIGO NO CERRADO CENTRAL 2 RESUMO O atendimento da demanda crescente por alimentos depende diretamente da irrigação. Neste cenário, o manejo eficiente dos recursos hídricos e o entendimento da variação temporal e espacial da evapotranspiração real das culturas (ETa) é essencial. Nas últimas décadas, modelos para monitoramento e mapeamento da ETa usando dados de sensoriamento remoto foram desenvolvidos. Neste trabalho, a performance do modelo Simple Algorithm for Evapotranspiration Retrieving (SAFER) foi avaliada para estimativa da evapotranspiração de duas culturas anuais irrigadas de inverno, no Cerrado. Para tal, utilizaram-se imagens multiespectrais e termais dos sensores ETM+/Landsat 7 e OLI-TIRS/Landsat 8. Inicialmente, o modelo foi calibrado para o trigo, sendo testado em seguida para o feijão, utilizando como referência dados de ETa obtidos pelo método da razão de Bowen. Após a calibração, o coeficiente de determinação (r²) encontrado foi igual a 0,91 e a raiz do erro quadrático médio (RMSE) igual a 0,58 mm d-1, para o trigo. Para o feijão, o r² foi igual a 0,65 e a RMSE igual a 0,77 mm d-1. Os resultados são satisfatórios, porém, sugerem que uma performance melhor pode ser obtida ao adotar-se uma calibração específica por cultura e/ou região, ou uma calibração em dois estágios, para valores de NVDI baixos e altos. Palavras-chave: sensoriamento remoto, recursos hídricos, irrigação, Cerrado.